Analysis of the Ability of School Supervisors in Increasing the Supervision of School Principals of Junior High School at Pidie District - Basri Basri (BIRCU, 2019)
The background of this research is related to the development of the direction of the ability of school supervisors, especially school principals at the junior secondary level, which are influenced by internal factors including: the level of readiness of supervisors, principals, curriculum devices, administration and management, then the readiness of external factors which include: lack of available amenities; the lack of disciplines in accordance with the situation in the field as an effort to support the achievement of better education and teaching. The method used is descriptive meaning to describe the factors that affect the ability of school supervisors competency of the Principal in Pidie District. Data collection techniques used were observation, interview and documentary study techniques, while the research subjects were supervisors, principals, totaling 20 people. The results showed that there were several factors that could influence the performance of school principals including: internal factors affecting the ability of supervisors, principals' competencies, among others, their level of education, experience and years of work, because this affected the level of readiness of school supervisors and principals in carrying out the activity. Then proceed with external factors that are considered to affect the ability of school supervisors, the competency of school principals, namely the availability of facilities and infrastructure as evidence to support the learning process, the achievement of learning directions as desired, improving the performance and supervision of school principals as well as adequate levels of welfare around 85,65%.